Pertinencia de aplicabilidad del acusador privado en la transformación de la acusación pública a acusación privada conforme a la Ley 1826 de 2017 (2020)
With the creation of Law 1826 of 2017, the decongestion of the judicial system in criminal matters in Colombia is intended, through the execution of the figure of the private accuser. This article seeks to review the implementation of Law 1826 of 2017 in the city of Medellín in order to determine the usefulness of transforming the public prosecution into private, taking a look at the impact that the aforementioned law has within the Colombian legal system through a national and local diagnosis. In the face of consultation about the purpose of this law, it is necessary to remember that beyond trying to create a procedural tool for decongestion, one should inquire about the side effects that consume this standard due to the regulatory impact that goes beyond a modification in the Code. Criminal, it is also necessary to assess whether the same representation is useful based on data measured by the victim's records of interest to the new abbreviated criminal procedure.